Mosquito fauna of the Guapiaçu Ecological Reserve, Cachoeiras de Macacu, Rio de Janeiro, Brazil, collected under the influence of different color CDC light traps. Issue 2 (December 2014) - Silva, Júlia dos Santos; Souto Couri, Márcia; de Leão Giupponi, Alessandro Ponce; Alencar, Jeronimo
ABSTRACT The objective of the present study was to identify mosquito fauna and to evaluate whether different light bulb colors influence the attraction of light traps in the Guapiaçu Ecological Reserve. Samples were obtained monthly during the period of February, 2012 to January, 2013. Centers for Disease Control (CDC) light traps with incandescent light bulbs and LED (ultraviolet, blue, green, and red) bulbs were utilized. In total, 8, 170 specimens were captured, including 59 species. The presence of Anopheles nimbus (Theobald 1902) and Orthopodomyia fascipes Coquillet 1906 were recorded for the first time in the state of Rio de Janeiro. The green LED trap attracted the highest number of specimens and presented the highest diversity and mosquito average. The blue and green LED traps attracted the highest number of species. However, the differences between lights were not significant. The most common species were Coquillettidia juxtamansonia (Chagas 1907), Culex declarator Dyar and Knab 1906, and Culex ribeirensis Forattini and Sallum 1985.